Pencegahan Karies Gigi Dengan Aplikasi Art (Atraumatic Restorative Treatment) Pada Gigi Molar Pertama Permanent Di Sdn Kurau Kabupaten Tanah Laut Propinsi Kalimantan Selatan - Kisworo Utami, Naning; Amperawati2, Metty; Salamah, Siti; Rahmawati, Ida; Nuryati, Sri; Elman Efzi, Agno; Nisa, Hilwatun; Yusril Pratama, Muhammad (Jurnal Rakat Sehat : Pengabdian Kepada Masyarakat, 2023)
ABSTRACT Based on caries history and caries lesion white spot is known as the best indicator in determining caries development. However, these indicators cannot reach the target accuracy of around 80%. Caries or cavities are problems that are often found in the oral cavity. According to WHO global data (2000) shows 60-90% of school children in industrialized countries have cavities. Based on the results of the 2007 Riskesdas in the province of South Kalimantan, the percentage of the population with dental and oral problems was 29.2%.This activity aims to identify def-t, DMF-T, carry out promotive, preventive and curative, namely by counseling, mass toothbrushes and filling applications with ART fillings on permanent first molars for students at SDN Kurau, Tanah Laut Regency, South Kalimantan Province . The community service target is 100 students. However, only 44 students and 12 parents attended. The results of the def-t examination obtained d = decay or dental caries of 165, e = extraction or teeth that could not be treated 97 teeth and f = fillings was 0, so the number of def-t was 350 teeth with an average of 7.98. Whereas the DMF-T had 80 teeth with an average of 1.82. The caries rate for primary and permanent teeth was high, that is, each child had 7-8 cavities for primary teeth while permanent teeth had cavities 2. Restoration with ART materials that can performed as many as 72 teeth. And 2 months later an evaluation was carried out, the results obtained were that 68 teeth were still holding on with the ART fillings, while 4 teeth had fallen out. The fact found in the field is that dental caries in primary teeth and permanent teeth is still very high, namely 143 teeth and 80 teeth in students of SDN Kurau, Tanah Laut Regency and what can be done with ART restoration on permanent first molars and referrals to the puskesmas or The hospital performed pulpal treatment and tooth extraction. It is recommended to treat teeth that can still be treated, namely the collaboration of the teacher (school), parents and the health center. Keywords: Permanent First Molar Caries, Prevention, ART Restoration